Behavior, Demand and the Marketing Mix Factors in the Customer's Perspective on Decision to Use the People's Bank Project Loan Service of Government Saving Bank, Ban Dung Branch - Tiluang , Nantikan; Leejoeiwara , Bussagorn (Journal of Modern Learning Development, 2021)
This study aims to (1) study behavior and demand for the People's bank project loan, (2) study the marketing mix factors in the customer's perspective on the decision to use the people's bank project loan service of Government Saving Bank, Ban Dung branch. Data were collected from 400 respondents. The research was quantitative research. Tools used for data collection were questionnaires. The statistics used were frequency, percentage, mean, standard deviation. According to the research findings: 1. The service behavior and demand for the People's bank project loan found that most of the respondents used people's bank project loan service in the group type. The objective of using was an expense for consumption. The reasons for choosing this were the bank's reputation and credibility, the interest rates were lower than other banks. The loan amount wanted to borrow from 150,001 - 200,000 baht. 2. Marketing mix factors in the customer's perspective on the decision to use the people's bank project loan were high level in all dimensions, including customer value, cost to customer, convenience, caring, completion, and comfort. Except, communication dimension was moderate in terms of importance.